Algorithmic and high-frequency trading strategies: A literature review - Alexandru Mandes (Philipps-University Marburg, School of Business and Economics, 2016)
The advances in computer and communication technologies have created new opportunities for improving, extending the application of or even developing new trading strategies. Transformations have been observed both at the level of investment decisions, as well as at the order execution layer. This review paper describes how traditional market participants, such as market-makers and order anticipators, have been reshaped and how new trading techniques relying on ultra-low-latency competitive advantage, such as electronic "front running", function. Also, the natural conflict between liquidity-consumers and liquidity-suppliers has been taken to another level, due to the proliferation of algorithmic trading and electronic liquidity provision strategies.
Keywords: C10; C61; C63; G19; 330; algorithmic trading; high-frequency trading; electronic market making